2021
DOI: 10.1039/d0cb00175a
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific modification and segmental isotope labelling of HMGN1 reveals long-range conformational perturbations caused by posttranslational modifications

Abstract: Using protein semi-synthesis, segmentally isotope-labelled variants of nucleosome-binding protein HMGN1 were generated with site-specific posttranslational modifications to explore their structural and functional effects.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
(119 reference statements)
0
7
0
Order By: Relevance
“…This may have important implications especially if phosphorylation affects HMGB1 in a different or opposite manner than what we observed for O-GlcNAc. Importantly, not all PTMs can induce dramatic alterations to protein structure and function; for instance phosphorylation studies of the HMGB1-related protein HMGN1 have recently shown mild to neutral effects on DNA binding . Thus, understanding the direct effects of phosphorylation of HMGB1 at S100 will be a critical point of interest for future studies, as well as understanding the dynamics of these two PTMs in the context of living systems.…”
Section: Discussionmentioning
confidence: 99%
“…This may have important implications especially if phosphorylation affects HMGB1 in a different or opposite manner than what we observed for O-GlcNAc. Importantly, not all PTMs can induce dramatic alterations to protein structure and function; for instance phosphorylation studies of the HMGB1-related protein HMGN1 have recently shown mild to neutral effects on DNA binding . Thus, understanding the direct effects of phosphorylation of HMGB1 at S100 will be a critical point of interest for future studies, as well as understanding the dynamics of these two PTMs in the context of living systems.…”
Section: Discussionmentioning
confidence: 99%
“…EPL can be used for the ligation of isotopically 15 N-and 13 C-labeled protein fragments to unlabeled protein fragments with natural abundance isotopes. Segmental labeling is useful for heteronuclear NMR analysis of large proteins because of a significant decrease in the spectral complexity, as only the labeled protein segments are observed (Chu et al, 2020;Cowburn, Shekhtman, Xu, Ottesen, & Muir, 2004;Niederacher et al, 2021).…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…83 In a further example of segmental labelling by protein semisynthesis, the effects of site-specific acetylation and phosphorylation on the nucleosome-binding protein HMGN1 were recently investigated (Figure 4c). 84 Lys acetylation is catalysed by lysine acetyltransferases (KATs) and reversed by lysine deacetylases (KDACs). 89 Both enzymatic reactions can be monitored by NMR in real time, as they exhibit characteristic features on the Lys Nα and Nε in 1 H- 15 N correlation experiments.…”
Section: Rsc Chemical Biology Accepted Manuscriptmentioning
confidence: 99%
“…Open were introduced in a peptide comprising residues 1-10 of HMGN1(1-10). 84 After ligation of the N-terminal segment to the isotope-labelled, recombinant HMGN1 segment, the product was characterised by NMR spectroscopy. 1 H- 15 N HSQC NMR experiments revealed long-range perturbations in the chemical environment of the backbone residues, even in this intrinsically disordered protein (IDP).…”
Section: Rsc Chemical Biology Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation